Game design and development for startups in the Singapore market - Ham, Kai Jie (Nanyang Technological University, 2022)
Over the years, the digital gaming industry has boomed since the birth of the first video game in 1952. The introduction of game development engines in the late 1990’s has further propelled the ability of companies to create high end games. In the modern era, game development software has evolved to be easy to use, even by beginners in digital game design with little artistic talent. This report illustrates a study of such game development software and the complete design and development process of a Windows platform ruined city themed puzzle and role-playing game called Lost in Atlantia. The game is implemented using Unity3D game engine. The project achieves a smooth game scene and user interface. The report also illustrates the design of various game interactions and how the functions are implemented using C# programming language. The development of this project adopts prototyping methodology.